Divergent office interior design for two different purposes - Nikoljski panevski, Elena; Zejnelabedin, Aziri (Ss. Cyril and Methodius University in Skopje, Faculty of Design and Technologies of Furniture and Interior in Skopje, 2017)
With this paper it is made an analysis of the concepts for organization of one interior space with two different functions. The purposes of the interior determine the project. Interiors can carry on many different functions. The purpose of this research paper is to analyze the process of designing an office space, by comparing two companies/entities from different sectors, two completely different ways and approaches. Thus, to maximize the efficiency of the design process and minimize the time needed to resolve potential issues that may arise at work. The goal set, the efficiency of the design in office spaces is implicative for this topic and it involves all the elements of design: shape, dimension, colour, texture, light, proportion, scale, balance, harmony, composition, modularity. This analysis is made through strategic planning of the office space. With this analysis the users of the office space would have detailed overview of the space in which they should work the arrangement of the furniture and other inventory and also of the way the employees are being arranged in the company and what conditions are provided to them. Also there is a short overview of the ergonomic principles that can be applied. With this method a detailed analysis is provided over the concepts for the organization and furnishing with furniture of office spaces.
Keywords: design; concept; organization; office space; diversity; functionality